Robust topology optimization of continuum structures subjected to uncertainties in the excitation frequency - Valentini, Fernando (2021)
This work studies the robust design of structures with minimum dynamic response (non-resonant structures) and maximum dynamic response (resonant structures) consideringuncertainty in the excitation frequency, using topology optimization. The Monte CarloSimulation method with stratified sampling is used to model both the expected value andstandard deviation of the structural dynamic response, described by a density-weightednorm. Results show that the proposed formulation leads to the design of structures withoptimized dynamic response and improved robustness, which is attested by comparisonwith the deterministic approach.Results also show that the mechanisms used to increase the robustness depend on thetarget frequency. For minimization cases, at low frequencies, a mode separation mechanismis preferred, while for higher frequencies, low energy resonant modes are used. Formaximization cases, there is also dependency on the excitation frequency, however, ina lower scale. In general, subsequent high-energy resonances located before and afterthe target excitation frequency improve response robustness while ensuring a resonatingbehavior within the interval bounded by the mentioned subsequent resonant modes.